Control of Third Order Processes Using Optimized Synthesis PI Controller - Suganya, G; Govinda Kumar, E (International Journal of Engineering and Technology, 2018)
Â In closed loop system with PI controller, the most and severe problem is peak overshoot minimization in the closed loop response and tuning the proportional plus integral (PI) controller parameters. This paper deals with the two different tuning methods for obtain the PI controller settings. These methods are used to tune the parameters of PI controller and the closed loop performances of two methods are analyzed for the control of third order processes. From the closed loop responses, the time responses are move to unstable characteristics and the process variables are oscillates due to PI parameters are tuned using Ziegler-Nichols method and direct synthesis method respectively. The control loop performance of the control of third order process is improved with optimized parameters of PI controller. In direct synthesis method, the variable parameter of PI controller is obtained with Genetic algorithm. The controller parameter of PI controller is obtained from optimized variable parameters and results are reveals that the performance of closed loop is enhanced with the elimination of peak overshoot and minimization of oscillation levels in the process variables. Simulation results are confirmation that the proposed design method is better to the Ziegler-Nichols method and direct synthesis method. Furthermore, the proposed method was applied to the control of two different categories of third order processes.Â Â